RETRACTED: Pierre Cardin and the Legal Battle for Well-Known Marks: Insights from Indonesia and the Netherlands - Sujatmiko, Agung; Haq, Hayyan Ul; Romadhona, Mochamad Kevin; Antons, Christoph (Hasanuddin Law Review, 2024)
Retraction notice: This article has been retracted at the request of the Editor-in-Chief due to concerns related to authorship issues.This work is aimed at reexamining the well-known mark protection, particularly in Indonesia. It is sparked by a substantive gap, covering theoretical and practical elements in protecting well-known mark. The case rooted at the Indonesian Supreme Court decision that refers to the constitutive systems in mark registration and refused the Pierre Cardin proposal to invalidate the Indonesian local that used mark Pierre Cardin for his convection products. Normatively, the court should analyze and consider the architecture of norms in protecting well-known mark by going further into the international conventions on mark, such as TRIPs agreement and Madrid Protocol that recognize and protect the well-known mark. To analyze this case, this work will apply normative legal research. In the discussion section, this work elaborates the basic concepts of well-known mark, fundamental and core elements as well as the indicators or criteria of well-known mark. In addition, this work will compare some jurisprudences concerning the well-known mark protection. At the end, this work offers some substantive and pragmatic approaches in strengthening well-known mark protection. The substantive approach will discuss and examine some theories, norms, and policies used by judges in handling well-known mark cases. Whereas, the pragmatic approach underlines the importance of institutional networking and legal awareness improvement, particularly key society groups, e.g., university and industry, to control violation of well-known marks.